BILIMLENDIRIW SAPASÍN ARTTÍRÍWDÍŃ ÁHMIYETLI FAKTORÍ SÍPATÍNDA SUMMATIV BAHALAWDÍŃ NÁTIYJELILIGI HÁM ABZALLÍLARÍ - Amanbaev, Muratbay Abdimuratovich; Yeshanova, Sapura Tazabayevna (ILIM hám JÁMIYET, 2026)
This article examines the role of summative assessment in the educational process and its contribution to improving educational quality. The theoretical foundations, international experience, and practical significance of summative assessment are analyzed. The findings indicate that summative assessment is an effective mechanism for measuring learning outcomes, ensuring educational accountability, and improving educational quality.